“I don’t think” versus “I think + not” - Sabet, Peyman G.P.; Zhang, G. (De Gruyter, 2017)
This paper explores an overlooked yet intriguing phenomenon: the different preferences of first language (L1) and second language (L2) groups in the use of I don’t think and I think+not. Based on naturally occurring data from linguistically and culturally contrastive groups of American English speakers, Chinese and Persian English speakers, this study finds that I don’t think highlights the speaker’s opinion, and I think+not focuses on the content conveyed. There is a correlation between the negative power and the distance between I think and the negative marker: the closer the two, the stronger the negativity. While I don’t think has more negativity force, I think+not has more mitigating weight and can be employed as a politeness strategy. The L1 speakers differ from the L2 speakers but are closer to the Chinese than the Persians; the striking variations occur between the L1 speakers and the Persians. The Persians are found to be the most indirect; the Chinese are more direct than the Persians but less direct than the L1 speakers. The differences between L1 and L2 groups relate to the first-language transfer and cultural influence. This study implies that different varieties of English use need to be addressed in language teaching.